2018
DOI: 10.1111/cns.12800
|View full text |Cite
|
Sign up to set email alerts
|

Incapacity to control emotion in major depression may arise from disrupted white matter integrity and OFC‐amygdala inhibition

Abstract: Our findings suggest that pathways connecting these two nodes may be core targets of the antidepressant treatment. In particular, it raised the intriguing question: Does the reversal of structural markers of connectivity reflect a response to antidepressant medication or activity-dependent myelination following a therapeutic restoration of effective connectivity?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…The UF is an association fiber extending from ventromedial prefrontal (vmPFC) regions to the amygdala, permitting bi-directional communication. Integrity of this tract has been associated with Stroop task performance (He et al, 2016; Schulte et al, 2012); more broadly, it is involved in emotion regulation (d’Arbeloff et al, 2018; Zheng et al, 2018). Disruptions in UF integrity have been linked to mood, anxiety, and trauma-related disorders (Lindner et al, 2018; Jenkins et al, 2016; Koch et al, 2017; Liao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The UF is an association fiber extending from ventromedial prefrontal (vmPFC) regions to the amygdala, permitting bi-directional communication. Integrity of this tract has been associated with Stroop task performance (He et al, 2016; Schulte et al, 2012); more broadly, it is involved in emotion regulation (d’Arbeloff et al, 2018; Zheng et al, 2018). Disruptions in UF integrity have been linked to mood, anxiety, and trauma-related disorders (Lindner et al, 2018; Jenkins et al, 2016; Koch et al, 2017; Liao et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Disruption in WM maturation leads to abnormal brain function correlated with numerous neuropsychological disorders . Furthermore, WM injury occurs in various CNS conditions/diseases, such as attention deficit‐hyperactive disorder, autism, multiple sclerosis, Alzheimer's disease, TBI, and stroke .…”
Section: Discussionmentioning
confidence: 99%
“…For example, patients with major depressive disorder show dysfunction in the orbitofrontal–AMY (OFC-AMY) structure and effective connectivity in the left hemisphere. 12 Another research study has suggested that depressed type 2 diabetes mellitus patients present decreased AMY FC in the cingulate cortex, the frontal lobe, and the precentral gyrus as well as a decrease in FC in the anterior cingulate cortex associated with the clinical depression score. 13 Similar AMY FC abnormality was also observed in individuals with Parkinson’s disease 14 and end-stage renal disease.…”
Section: Introductionmentioning
confidence: 99%